Repellent constituents of essential oil of Cymbopogon distans aerial parts against two stored-product insects - Zhang, Jing Song; Zhao, Na Na; Liu, Qi Zhi; Liu, Zhi Long; Du, Shu Shan; Zhou, Ligang; Deng, Zhi Wei (Journal of agricultural and food chemistry, 2011)
The screening for bioactive principles from several Chinese medicinal herbs showed that the essential oil of Cymbopogon distans aerial parts possessed strong repellency against the booklouse, Liposcelis bostrychophila , and the red flour beetle, Tribolium castaneum . A total of 36 components of the essential oil were identified by GC and GC-MS. trans-Geraniol (16.54%), (R)-citronellal (15.44%), (+)-citronellol (11.51%), and α-elemol (9.06%) were the main components of the essential oil followed by β-eudesmol (5.71%) and (+)-limonene (5.05%). From the essential oil, four monoterpenes were isolated by bioassay-guided fractionation. The compounds were identified as limonene, citronellol, citronellal, and trans-geraniol. Geraniol and citronellol were strongly repellent against the booklouse, L. bostrychophila, whereas citronellal and limonene exhibited weak repellency against the booklouse. Geraniol and citronellol exhibited comparable repellency against the booklouse relative to the positive control, DEET. Moreover, geraniol and citronellol exhibited stronger repellency against the red flour beetle than DEET, whereas the two other compounds showed the same level of repellency against the red flour beetle compared with DEET.